The reading-writing relationship: Three teaching approaches designed using reading and writing activities to develop persuasive discourse in adult ESL writing. - Beare, Sophie. (University of Ottawa (Canada), 1993)
This thesis examines the supportive relationship between reading and writing. Using persuasive discourse structure, the study explores whether reading and writing taught together in context enhance writing more than if each of these modes is taught separately. The thesis focuses on the interactive approach to reading and writing as explained by Shanahan (1984). To explain the structure of the persuasive mode in writing Kinneavy's (1983) classification of discourse types is used. According to Kinneavy (1983) the writer's purpose establishes the discourse type. He states "The aims of discourse determine everything else in the process of discourse" (p. 48). The study examined the hypothesis that using both reading and writing activities improves writing more than using reading or writing activities separately. Thirty-seven students from Intermediate ESL levels participated in this project. The subjects were divided into three groups: Reading, Writing, and Reading and Writing Group. Univariate statistics were computed on the pre-post difference scores to investigate the effects of the three approaches to writing. In the results, it was found that Reading and Writing group showed gains, although non-significant, in discourse structure whereas the other two did not show the improvement. Since it was difficult to control for L$\sb2$ proficiency as intermediate students may have possessed varied L$\sb2$ proficiency levels, this research explored whether the writing effectiveness was constrained by low L$\sb2$ proficiency. Thus the research question dealing with correlation between L$\sb2$ proficiency and the results on the writing tasks revealed a positive correlation, although non-significant.
Keywords: Education, Language and Literature.